A novel filtration method for cord blood processing using a polyester fabric filter. Issue 4 (14th December 2012) - Shima, T.; Forraz, N.; Sato, N.; Yamauchi, T.; Iwasaki, H.; Takenaka, K.; Akashi, K.; McGuckin, C.; Teshima, T.
Summary Introduction Cord blood (CB) is being increasingly used as a source of hematopoietic stem cells for transplantation to treat diseases of the blood and immune systems, and there is an urgent need to expand CB banking worldwide. CB processing requires costly machinery or a clean room that hampers wider application of CBT particularly in the developing countries. Methods We developed a novel filtration system using a nonchemical‐coated and nonwoven polyester fabric filter, which traps cells through affinity and does not require centrifugation or potentially toxic chemicals. Results Cell processing with the device resulted in minimum cell loss of total cells and CD34+ cells, without impairing the ability of CD34+ cells to engraft and differentiate both in vivo and in vitro. Conclusion CB processing with this device is simple, cost‐effective, and nontoxic without requiring costly equipment will thus facilitate international CB banking, which helps in meeting the increasing worldwide demand for CB for allogeneic hematopoietic stem cell transplantation.